Ռիսկերի դասակարգումը և դրանց կառավարման փուլերը - Ռուզաննա Ստեփանի Ալոյան (ՀՀ ԳԱԱ հրատ.)
Таким образом, при классификации рисков важно следовать принципу, согласно которому классификация рисков должна разрабатываться отдельно для каждого вида деятельности в зависимости от объема деятельности и степени сложности. Одновременно с классификацией рисков очень важно иметь эффективное научно-обоснованное управление. Отсутствие эффективных структур управления рисками в рамках процесса принятия решений приводит к нежелательным последствиям и банкротству крупнейших компаний. Thus, while classifying various types of risks the following principle needs to be applied: for each type of economic activity respective risks need to be identified and classified, depending on the specifics and complexity of the given type of activity. Along with risk classification, the effective and scholarly-grounded methods on the management of thereof are highly stressed. The lack of institution and or unit being in charge of effective risk management as a part of decision-making system leads to undesirable consequences and bankruptcy of large companies.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ